Physical fitness modulates mucosal immunity and acceleration capacity during a short-term training period in elite youth basketball players - Valvassori, R.; Saldanha Aoki, M.; Conte, D.; Drago, G.; Moreira, A. (Science & Sports, 2020)
This study aimed to investigate the effect of physical fitness level (Yo-Yo intermittent recovery test level 1 [Yo-Yo IR 1]) and initial stress level (salivary cortisol [SC]) on salivary immunoglobulin A secretion rate (SIgArate), and the influence of physical fitness on accelerations (external training load; eTL) and training impulse (TRIMP; internal training load; iTL), in 20 elite youth male basketball players (14.5 ± 0.5 years; height, 177 ± 10 cm; body mass, 69 ± 13 kg) following a short-term training stress (two daily consecutive basketball-training sessions). Saliva samples were collected before and after the experimental period. A multiple linear regression analysis was conducted using the Yo-Yo IR 1 and SC as independent variables, and changes in SIgArate as dependent variable. The Yo-Yo IR 1 was the only statistically significant variable (R = 0.73; P = 0.001). Participants were divided a posteriori into high fitness (HFG) and low fitness (LFG) groups according to the median-split technique, taking the Yo-Yo IR 1 performance into account, to compare the eTL and iTL. HFG performed a higher total eTL (34 ± 13 vs. 17 ± 7 accelerations; t = 3.4; P = 0.003) but no difference between fitness groups was observed for TRIMP (t = 0.33; P = 0.74). The results suggest that physical fitness level may play a role on mucosal immunity responses from short-term training stress in youth basketball players. Players with greater level of physical fitness are likely to perform a higher training load without inducing higher stress levels.